A Response to Dr. Hartley’s Presidential Address – ASM 2024 - Kach-Yawnghwe, Allison (Missiology, 2025)
The author reflects on some of the missiological insights from the life of John R. Mott, in response to Dr. Hartley’s presidential address to the American Society of Missiology at the 2024 Annual Meeting.